An iterative procedure for analyzing a combination of censored and uncensored traits in mixed models: Estimation of location parameters - Togashi, K.; Rege, J.E.O. (1997)
A mixed model simultaneous procedure is described to estimate location parameters for the right-censored and uncensored traits in the practical animal breeding data set for herd-life and milk production. Location parameters of fixed effects represented by herd -year effects and random effects represented by sire additive genetic effects were given as the mode of posterior distribution resulting from a combination of a multivariate normal density and a standard normal cumulative distribution function. An iterative method for solving mixed model equations is presented for this kind of data analysis without explicitly setting up the equations.